2021
DOI: 10.5946/ce.2020.226
|View full text |Cite
|
Sign up to set email alerts
|

Is Submucosal Injection Helpful in Cold Snare Polypectomy for Small Colorectal Polyps?

Abstract: Background/Aims: Cold snare polypectomy (CSP) is an effective method of polyp removal for small colorectal polyps. However, the effect of submucosal injection in cold snare endoscopic mucosal resection (CS-EMR) for small polyps is unclear. Therefore, this study aimed to evaluate the effect of submucosal injection in CS-EMR for small polyps. Methods: Between 2018 and 2019, 100 consecutive small colorectal polyps (5-10 mm) were identified in 58 patients. The first 50 consecutive polyps were removed by CS-EMR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Ultimately, 12 studies were included (Fig. 1 and Table I) [9][10][11][12][13][14][15][16][17][18][19][20]. None of these studies reported receiving industry funding.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Ultimately, 12 studies were included (Fig. 1 and Table I) [9][10][11][12][13][14][15][16][17][18][19][20]. None of these studies reported receiving industry funding.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The sample size of these studies ranged between 55 and 605,044. Of the 12 studies, 10 studies were retrospective cohort studies [9,[11][12][13][14][15][16][17][18]20], one was a prospective cohort study [10], and one was a randomized controlled trial (RCT) [19]. Three studies were conducted in China [14,16,18], two were conducted in the USA [9,10], and the others were conducted in Japan [11-13, 15, 17, 19, 20].…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations